A Zn:BiVO4/Mo:BiVO4 homojunction as an efficient photoanode for photoelectrochemical water splitting. Issue 15 (26th March 2019) - Lee, Jae Myeong; Baek, Ji Hyun; Gill, Thomas Mark; Shi, Xinjian; Lee, SangMyeong; Cho, In Sun; Jung, Hyun Suk; Zheng, Xiaolin
Abstract : Photoelectrochemical (PEC) water splitting has been extensively studied as a method to convert sunlight and water to hydrogen. Abstract : Photoelectrochemical (PEC) water splitting has been extensively studied as a method to convert sunlight and water to hydrogen. Among the many obstacles facing PEC water splitting, a critical challenge is the lack of efficient photoanodes for the water oxidation reaction. Here, we report an n–n + type-II homojunction of Zn:BiVO4 /Mo:BiVO4, which improves the bulk transport and surface charge transfer processes of the well-studied BiVO4 photoanode. In this homojunction, the Zn and Mo dopants move the BiVO4 valence band maximum and conduction band minimum, respectively, closer to the Fermi level, establishing an n–n + type-II homojunction. The staggered band alignment between Zn:BiVO4 and Mo:BiVO4 facilitates electron–hole separation between the two layers. The Mo dopant increases the donor concentration, leading to higher electrical conductivity. The Zn dopant increases the number of oxygen chemisorption sites, improving the interfacial charge transfer process. With additional deposition of the oxygen evolution electrocatalyst Ni:FeOOH, the homojunction achieves charge transport and transfer efficiencies of 65% and 89%, respectively. The final Ni:FeOOH/Zn:BiVO4 /Mo:BiVO4 photoanode achieves a photocurrent density of 2.7 mA cm −2 and a faradaic efficiency for oxygen evolution of ∼92% at 1.23 V vs. RHE in the electrolyte of potassium buffer solution (pH ∼ 7).